1977
DOI: 10.1007/bf01236309
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proinsulin, C-peptide and insulin in diagnostic suppression tests for insulinomas

Abstract: Summary. The value of plasma insulin, human Cpeptide and proinsulin estimation in the diagnosis of 15 insulinomas has been investigated. Measurement of plasma proinsulin in an overnight fasting sample diagnosed all the insulinomas studied, irrespective of the plasma glucose. Patients with insulinomas had plasma proinsulin in the range 0.04-4.2 pmol/1 and normal values were less than 0.01 pmol/ml. If hypoglycaemia was present, an inappropriately raised plasma immunoreactive insulin (including proinsulin) was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Thus, in hyperthyroidism it could be argued that the pancreatic B cell has an increased capacity to secrete proinsulin compared with the euthyroid state, and proinsulin is circulating in high concentrations because of the relatively slow rate of proinsulin removal [15,16]. In contrast to insulin independent diabetes, where the fasting proinsulin concentration is also increased [17], the concentration of proinsulin in thyrotoxicosis is frequently so high that it is in the range which is considered characteristic of patients with insulinomas [14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in hyperthyroidism it could be argued that the pancreatic B cell has an increased capacity to secrete proinsulin compared with the euthyroid state, and proinsulin is circulating in high concentrations because of the relatively slow rate of proinsulin removal [15,16]. In contrast to insulin independent diabetes, where the fasting proinsulin concentration is also increased [17], the concentration of proinsulin in thyrotoxicosis is frequently so high that it is in the range which is considered characteristic of patients with insulinomas [14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the use of today's specific and sensitive insulin assays, any detectable circulating insulin during neuroglycopenia already reflects inappropriate hyperinsulinemia [12][13][14]. Thus, proinsulin should be determined in any patient during neuroglycopenia [15][16][17][18][19]. Because of these facts endocrinologists and surgeons have become alert to interpret the results of fasting tests in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…Service et al reported that insulinoma patients had C-peptide values at the end of the 72 h fasts greater than or equal to 0.20 nmol/mL (0.60 ng/mL); however, our case does not fulfill that criterion even before conducting the prolonged fasting test [12]. According to the data from the literature, the molar ratio of serum C-peptide to insulin is, in general, decreased in patients with insulinoma than normal subjects, while in our case the ratios were much lower (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 91%